2015
DOI: 10.14260/jemds/2015/2337
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ketorolac, Diclofenac and Paracetamol for Postoperative Analgesia Following Abdominal Hysterectomy

Abstract: BACKGROUNDAbdominal hysterectomy is associated with moderate-to-severe postoperative pain. Among non-opioid analgesics diclofenac, paracetamol and ketorolac are most commonly used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This clearly appeared in three previous studies done in different countries showing that ketorolac had a higher analgesic effect than diclofenac and paracetamol after surgery (44)(45)(46) , and also agrees with another retrospective study in 2016 showing that ketorolac after appendectomy significantly decreases the pain score during the first day of surgery in pediatric patients (47) . This conclusion was also presented with different surgical procedures both in adults (48)(49)(50) and children (47,50) . Another study in Korea showed that iv paracetamol (1g) has the same level of pain relief after surgery as iv ketorolac (30 mg) in patients who underwent thyroidectomy, this made paracetamol an effective alternative to ketorolac in case of mild to moderate pain after surgery (51) .…”
Section: Discussionmentioning
confidence: 70%
“…This clearly appeared in three previous studies done in different countries showing that ketorolac had a higher analgesic effect than diclofenac and paracetamol after surgery (44)(45)(46) , and also agrees with another retrospective study in 2016 showing that ketorolac after appendectomy significantly decreases the pain score during the first day of surgery in pediatric patients (47) . This conclusion was also presented with different surgical procedures both in adults (48)(49)(50) and children (47,50) . Another study in Korea showed that iv paracetamol (1g) has the same level of pain relief after surgery as iv ketorolac (30 mg) in patients who underwent thyroidectomy, this made paracetamol an effective alternative to ketorolac in case of mild to moderate pain after surgery (51) .…”
Section: Discussionmentioning
confidence: 70%
“…A research by Kumar et al, found that intravenous paracetamol and intravenous ketorolac reduced post-operative pain in patients having gynaecological abdominal surgery (hysterectomy) by 2.25 ± 0.44 and 1.88 ± 0.34, respectively 15 . Further research by Kumar G et al compared the effectiveness of ketorolac 30mg IV to that of diclofenac 75mg IV and paracetamol 1gm IV, and showed that patients who got ketorolac had a considerably lower VAS score than those who received diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory medication (NSAID) ketorolac is. It has been found to have opioid sparing effects and is utilised for the short-term treatment of moderate to severe pain by lowering the synthesis of prostaglandins 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Usage of ketorolac significantly lower pain score even after few days of appendectomy. This indicates that ketorolac has higher efficacy and analgesic potency than other NSAIDS as it readily available to the body and its rapid onset of action 21 .…”
Section: Discussionmentioning
confidence: 99%